Pengaturan Jaminan Sosial Ketenagakerjaan bagi Pekerja Informal pada Masa Pendemi Covid 19 - Made Danang Mahendra Gama; I Nyoman Putu Budiartha; Ni Made Puspautari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2022)
This study aims to analyze and describe the social security arrangements for informal workers during the COVID-19 pandemic. This research belongs to the type of normative legal research using a contextual approach, with the source of data coming from literature studies, data collected by recording and sorting information methods. Furthermore, the data were analyzed by descriptive method. The results of the study indicate that in carrying out their lives, people are no stranger to human rights where human behavior must not interfere with the rights of others and do not behave outside the norms that apply in accordance with positive law. The results of the study show that in 2021 the world will be hit by a pandemic that makes some workers have to rest due to the decline in the economic value of a country due to the Covid-19 pandemic which until now has hit without knowing when it will end. The government, in this case, regulates regulations related to the dangers of Covid-19 and its very fast transmission, causing many fatalities, especially among the elderly and the elderly due to a decrease in their immune system.